The Effect of Giving Mangosteen Peel Extract (Garcinia mangostana L.) in Drinking Water on Broiler Performance - O. B. I. P. A, Yanesti; Astawa, Astawa; Sumadi, I. K; Bulkaini, Bulkaini; Kisworo, Djoko (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangosteen peel is a waste that can be used as a feed additive. The function of xanthones in mangosteen peel as anti-tumoural, antioxidant, anti-inflammatory, anti-allergic, anti-microbial, anti-fungal, and anti-virus. The research aims to determine the effect of administering mangosteen peel extract in drinking water on the performance of broiler chickens for 35 days which was carried out in Dajan Peken Village, Tabanan District, Tabanan Regency, Bali. The design used was a Completely Randomized Design (CRD) with 4 treatments and 4 cage units as replications. Each cage unit contains 4 broiler chickens so that the total research material is 64 broiler chickens aged 11 days. Drinking water treatment: drinking water without mangosteen peel extract as control (P0), drinking water containing 1% (P1), 2% (P2), and 3% (P3) mangosteen peel extract. The variables observed were initial body weight, final body weight, body weight gain, ration consumption, ration conversion, drinking water consumption. The results showed that the final body weight in treatment P1 (2.108.3 g/head) with an increase in body weight of 1.627.4 g/head was higher than in treatments P0, P2, and P3 but was not significantly different (P>0.05) with the lowest ration conversion value (1.54). Drinking water consumption in treatment P1 (5.556.2 ml/head) was higher than in treatments P0, P2, and P3) and significantly different (P<0.05) from treatment P0 (4.628ml/head). Conclusion: Providing mangosteen peel extract (Garcinia mangostana L.) in drinking water at a level of 1% can provide optimal results to improve broiler performance and reduce feed conversion.